Differences of methacrylate and silorane based composite resins surface hardness after 40% hydrogen peroxide application - Putri, Amalina; Adang, Rahmi Alma Farah; Hidayat, Opik Taofik (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2013)
Composite restoration is frequently found on teeth before doing any bleaching treatment. Hydrogen peroxide is a bleaching agent which enable transition to one of the composite physical properties. The aim of this research was to observe the difference of surface hardness between methacrylate and silorane based composite resin after application of 40% hydrogen peroxide. This true experiment involved 36 specimens from two different disc-shaped methacrylate and silorane based composite resins, with 18 specimens methacrylate and 18 silorane. Every specimen groups were immersed in artificial saliva solution and divided into two groups; the first group consisted of 9 specimens of control which were tested directly using microvickers hardness tester and another group consisted of 9 specimens which had been added by 40% hydrogen peroxide for hardness test. The result showed the different surface hardness average value of metachrylate and silorane based composite resin after application of 40% hydrogen peroxide. The surface hardness of methacrylate and silorane based composite resins was 41.8 VHN and 33.7 VHN (p>0.05) with t-test, respectively. From this study concluded that there was no significant difference between methacrylate and silorane based composite resins after 40% hydrogen peroxide application.